A Study on Customer Perception of Medical Tourism in Puducherry - Marie, C Shanthi; Swain, Sampad Kumar (Atna Journal of Tourism Studies, 2017)
Medical tourism is the latest trend happening in many countries of the world where tourists in need of medical treatments from the developed countries approach the developing countries imparting treatments at par with the quality of their home countries. Among the countries practicing medical tourism, India is occupying one of the top positions with respect to the quality treatments as most of the states have recognized its significance. This study aims at studying the customer perception of medical tourism in the union territory of Puducherry. The units of the study are the international medical tourists who sought medical treatments in the private healthcare hospitals of Puducherry. The methodology used for the study is descriptive, analytical and inferential. Factor Analysis, T-test and ANOVA are the tools utilized for analyzing the primary data. The study reveals that the facilities provided to foreign patients are customer oriented. The satisfaction level of patients regarding the staff interaction, facilities and amenities and treatment are high. But, there is some need of improvement in the case of formalities and tourism part. The efficiency of the doctors, their personal touch, their communication skills, the facilities and amenities of the hospitals contributes to the cutting edge experience by the medical tourists. One important drawback is the lack of international accreditation which needs utmost ground work. The study finally suggests strategies for motivating the medical tourists undertaking healthcare treatments in Puducherry.